POLA ASUH ANAK USIA DINI DALAM ISLAM - Hasanah Hasanah; Nur Aini Zaida (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2020)
The family is the smallest element of the country, the family is the first to carve ink on white paper that has not been filled in the life of a child and the family's biggest role in shaping the growth and development of early childhood as a devout Muslim family, religion is a way of life that must be integrated into activities our daily lives, as well as in parenting, need to be explored how to improve the growth and development of children through Islamic parenting. With a qualitative method through the library research approach, the author examines a variety of literature about parenting taught in Islam. The purpose of this study is to present measures or strategies of stimulation with Islamic nurturing in optimizing the growth and development of early childhood, and finally get the following conclusions: the first strategy is to maximize interaction with children, the second provides quality time for children. children, third parental role models, fourth focus on the good things of children, fifth do good habits and teach life skills to children. These five things can be used as a strategy to optimize the growth and development of children, because it is based on Islamic legal guidelines, in the history of the care of the family of the Prophet Muhammad, when he educated his children with his wife Siti Khadijah, their sons and daughters proved not only superior and have good character, but they are also missed by heaven.